Endometrial histology in severely obese bariatric surgery candidates: an exploratory analysis - Kaiyrlykyzy, Aiym; Freese, Kyle E.; Elishaev, Esther; Bovbjerg, Dana H.; Ramanathan, Ramesh; Hamad, Giselle G.; McCloskey, Carol; Althouse, Andrew D.; Huang, Marilyn; Edwards, Robert P.; Linkov, Faina (My University, 2015)
Abstract BackgroundEndometrial pathology risk has been linked to obesity; however, little is known of its prevalence in severely obese women not seeking care for endometrial pathology associated symptoms. This pilot study was designed to explore the frequency and risk factors associated with endometrial pathology in cancer-free, severely obese, bariatric surgery candidates using the Pipelle endometrial sampling technique (SureFlex Preferred Curette, Bioteque America, Inc, New Taipei City, Taiwan). MethodsTwenty-nine severely obese bariatric surgery candidates with intact uteruses and no history of endometrial cancer or endometrial ablation were included in this subanalysis from a larger cohort of 47. Endometrial samples were obtained using a Pipelle endometrial suction curette at a single time point before surgery. Logistic regression was used to assess the relationship between body mass index and endometrial pathology when adjusting for age and race. ResultsOf the 29 successful biopsies, 8 (27.6%) were classified as abnormal endometrium: 1 was classified as complex atypical hyperplasia, 1 was classified as hyperplasia without atypia, 4 samples were identified with endometrial polyps, and 2 samples were identified with metaplasia. None presented with cancer. Increasing body mass index was significantly associated with higher risk of abnormal endometrium (OR = 1.19, 95% CI [1.03–1.36], P = .01). ConclusionsThe findings in this sample suggest that obesity may be associated with increased risk of having undiagnosed endometrial pathology. More thorough examination of relationships between levels of obesity and endometrial pathology are needed to better characterize high cancer risk groups who may benefit from introducing new screening measures.
Keywords: Bariatric surgery; Endometrial cancer; Endometrial hyperplasia; Endometrial polyps; Obesity; Pipelle sampling